Postcolonial whiteness : a critical reader on race and empire - López, Alfred J., 1962- (Book collections on Project MUSE., 2005)
"Postcolonial Whiteness examines the interrelations between whiteness and the history of European colonialism, as well as the status of whiteness in the contemporary postcolonial world. It addresses two fundamental questions: What happens to whiteness after empire, and to what extent do white cultural norms or imperatives remain embedded in the postcolonial or postindependence state as a part - acknowledged or not - of the colonial legacy?"--Jacket